Fiscal redistribution and social welfare: Doing more or more to do? - David P. Coady; Devin D'Angelo; Brooks Evans (University of Essex, Institute for Social and Economic Research (ISER), 2020)
This paper embeds analysis of fiscal redistribution (FR) within the standard social welfare framework. Differences in FR are decomposed into differences in the magnitude (fiscal effort) and progressivity (fiscal progressivity) of transfers. Progressivity is further decomposed into differences in the distribution of transfers across income groups (targeting performance) and in the social welfare returns to targeting (targeting returns). This motivates a distinction between conditional and unconditional FR, where the latter abstracts from targeting returns. For illustrative purposes, the framework is applied to EUROMOD data for EU countries to explain differences in FR and to discuss patterns in FR highlighted in the literature.
Keywords: H22; H23; 330; Fiscal redistribution; progressivity; targeting; transfers; taxes